2006
DOI: 10.1089/lrb.2006.4406
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Lymphatic Function, And Dendritic Cell Migration

Abstract: The lymphatic system is not only essential for maintenance of normal fluid balance, but also for proper immunologic function by providing an extensive network of vessels, important for cell trafficking and antigen delivery, as well as an exclusive environment, the lymph node (LN), where antigen-presenting cells (APCs) and lymphocytes can encounter and interact. Among APCs, dendritic cells (DCs) have a remarkable capacity to traffic from peripheral tissues to the draining LN, which is critical for execution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 101 publications
2
99
0
5
Order By: Relevance
“…Our finding that 5-HT 7 R can modulate the migratory properties of mature dendritic cells suppose that impaired 5-HT 7 R-mediated signaling in dendritic cells might be involved in the pathogenesis of inflammatory diseases, which are often accompanied by reduced dendritic cell motility (Angeli and Randolph, 2006;Eriksson and Singh, 2008;Hermida et al, 2014). In our recent work, we have demonstrated that 5-HT 7 R-mediated signaling is crucially involved in the progression of chemically induced acute and chronic colitis in mice (Guseva et al, 2014).…”
Section: Discussionmentioning
confidence: 80%
“…Our finding that 5-HT 7 R can modulate the migratory properties of mature dendritic cells suppose that impaired 5-HT 7 R-mediated signaling in dendritic cells might be involved in the pathogenesis of inflammatory diseases, which are often accompanied by reduced dendritic cell motility (Angeli and Randolph, 2006;Eriksson and Singh, 2008;Hermida et al, 2014). In our recent work, we have demonstrated that 5-HT 7 R-mediated signaling is crucially involved in the progression of chemically induced acute and chronic colitis in mice (Guseva et al, 2014).…”
Section: Discussionmentioning
confidence: 80%
“…19,20 Molecular characterization of the tissues with lymphedema revealed the prominence of inflammatory mediators affecting the inflammatory nature of this acquired microvascular disorder. [21][22][23] Lymph stasis is known to induce the tissue destruction associated with lymphedema. Inflammation in lymphedema may be in response to loss of lymphatic vascular integrity, and thus a rational target for intervention in this experimental model.…”
Section: Discussionmentioning
confidence: 99%
“…the diameter of lymphatic capillaries increases while their density remains unchanged) [50]. In general, lymphatic hyperplasia and lymphangiogenesis have not been carefully distinguished in the literature, even though these are likely to have different effects on tissue fluid clearance and drainage to the lymph node [1,28,51]. Molecular mediators of lymphangiogenesis are well described in several recent reviews [1,52,53] and will not be discussed in detail here.…”
Section: Lymphatic Physiology and Neogenesismentioning
confidence: 99%
“…Transport of lymph to the draining LN is achieved in such a way as to optimize the delivery of pathogenic signals, antigens, and immune cells to promote antigen capture by B cells and DCs, and facilitate T cell education and priming [5,51] (Fig. 1).…”
Section: Secondary Lymphoid Organsmentioning
confidence: 99%
See 1 more Smart Citation